Phthalates removal from wastewater by different methods – a review. (21st April 2022) - Becky Miriyam, I.; Anbalagan, K.; Magesh Kumar, M.
Abstract: Phthalate esters are commonly used as plasticizers to improve the durability and workability of polymeric materials, locating and identifying them in various contexts has become a major challenge. Because of their ubiquitous use in plastic packaging and personal care items, as well as their tendency to leach out of these materials, phthalates have been detected in a variety of aquatic situations, including surface water, groundwater, drinking water, and wastewater. Phthalate esters have been shown to affect reproductive health and physical growth by disrupting the endocrine system. As a result, developing energy-efficient and effective technologies to eliminate these harmful substances from the atmosphere has become more important and urgent. This paper examines the existing techniques for treating phthalates and degradation mechanisms, as well as knowledge gaps and future research directions. These technologies include adsorption, electrochemical, photocatalysis, membrane filtration and microbial degradation. Adsorption and photo catalysis are the most widely used techniques for phthalate removal, according to the literature survey papers. HIGHLIGHTS: The existence of phthalates in wastewater are discussed. The aggressive effects due to the combined existence are summarized. Several technologies adopted for their simultaneous removal are reviewed. Different parameters used to study the removal efficiency are presented. The detection of pollutants by analytical techniques are defined. Graphical Abstract